2020
DOI: 10.1101/2020.05.25.115147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network linking scene perception and spatial memory systems in posterior cerebral cortex

Abstract: word count: 75 Main text word count: 1,913ABSTRACT Here, we report a new link between the spatial-memory and scene-perception systems of the human brain. Using fine-grained individual-subject fMRI, we describe three cortical areas, each lying immediately anterior to a region of the scene perception network, that are selectively activated when recalling familiar places. Network analyses show that these regions constitute a distinct functional network and interface with memory systems during naturalistic scene u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 113 publications
(201 reference statements)
3
6
0
Order By: Relevance
“…Similar posterior (perception) to anterior (memory retrieval) shifts have been observed in other sceneselective areas, including lateral occipital and medial parietal areas [14,28]. Resting state fMRI analyses have shown that anterior and posterior aspects of ventral, lateral, and medial sceneselective areas have different connectivity profiles with the rest of the brain, consistent with the idea that scene perception and scene memory are supported by segregated visual cortical networks [14,[27][28][29]. Related work has suggested that this posterior-to-anterior division between visual perception and visual memory extends to stimulus classes other than scenes, such as objects, and to aspects of lateral and ventral temporal cortex outside of the scene network [30,31].…”
Section: Trends Trends In In Neurosciences Neurosciencessupporting
confidence: 71%
See 4 more Smart Citations
“…Similar posterior (perception) to anterior (memory retrieval) shifts have been observed in other sceneselective areas, including lateral occipital and medial parietal areas [14,28]. Resting state fMRI analyses have shown that anterior and posterior aspects of ventral, lateral, and medial sceneselective areas have different connectivity profiles with the rest of the brain, consistent with the idea that scene perception and scene memory are supported by segregated visual cortical networks [14,[27][28][29]. Related work has suggested that this posterior-to-anterior division between visual perception and visual memory extends to stimulus classes other than scenes, such as objects, and to aspects of lateral and ventral temporal cortex outside of the scene network [30,31].…”
Section: Trends Trends In In Neurosciences Neurosciencessupporting
confidence: 71%
“…In an unpublished study, this striking dissociation was replicated in a paradigm that directly compared perception and memory retrieval using a within-subjects design [14]. Similar posterior (perception) to anterior (memory retrieval) shifts have been observed in other sceneselective areas, including lateral occipital and medial parietal areas [14,28]. Resting state fMRI analyses have shown that anterior and posterior aspects of ventral, lateral, and medial sceneselective areas have different connectivity profiles with the rest of the brain, consistent with the idea that scene perception and scene memory are supported by segregated visual cortical networks [14,[27][28][29].…”
Section: Trends Trends In In Neurosciences Neurosciencesmentioning
confidence: 90%
See 3 more Smart Citations